Muslim-friendly medical services : understanding of Hijamah practitioners in Klang Valley on Malaysian traditional and complimentary medicine guidelines - Mohamad Afiq Razali (International Institute for Halal Research and Training, International Islamic University Malaysia, 2021)
The Ministry of Health Malaysia (MOH) has established the Traditional and Complementary Medicines Division (TCM) in February 2004. The Ministry has recognised Ḥijamah therapy as one of the traditional and complementary medicines practices under this division. Under TCM Act 2016, the MOH is the only authority to govern the policy and impose the ethical practice guidelines on Ḥijamah practitioners in providing safe and clinically proven services as the best. Ḥijamah is expected to be one of the drivers in the global Halal treatment industry in Malaysia. This research explores how Ḥijamah practitioners respond and adapt to the latest policy from the TCM Division by MOH. This study uses semi-structured interviews in order to collect the data. The informal interviews with the Ḥijamah practitioners will question Ḥijamah issues and the practitioners’ awareness and acknowledgement of the existence and importance of the TCM rules and guidelines. This data collection provides the basis for future study on the perception and expectations of Ḥijamah service delivery in the rapidly growing Muslim-friendly medical care sector. On the whole, this thesis act as an effort for the revival of the Prophetic Medicine and importance for the practitioners to adhere to these guidelines for ensuring that the Maqaṣid al-Shar'iah, which protect a patient’s life, intellect and property, are safeguarded. All of this is in accordance with the basic purpose of a Muslim’s life: to obtain Allah SWT’s blessings in all circumstances. Practising Ḥijamah for a living is one kind of worship to Allah, which has to be undergone in a way that Allah SWT blesses.